2020
DOI: 10.1029/2020gl088269
|View full text |Cite
|
Sign up to set email alerts
|

The Reversal Indian Ocean Waters

Abstract: The Reversal Indian Ocean Waters (RIOWs), carried by flows in a direction opposite to the Indonesian Throughflow (ITF), is investigated in the Lagrangian framework using the simulative results of a high‐resolution western Pacific and northern Indian Oceans Model (PIOM). The results suggest that the RIOWs have two sources: They are the Australian Northwest Shelf Inflow linking with the Leeuwin UnderCurrent (LUC) along with the previously identified South Java Coastal Undercurrent (SJCU). After entering the Indo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…To follow the evolution of the air masses of the hot events backwards in time, we employ the Lagrangian trajectory model TRACMASS v7.0 (Aldama-Campino et al, 2020;Döös, 1995), which can be applied to study the atmospheric or oceanic circulation (e.g., Dey & Döös, 2020;Liang & Xue, 2020). TRACMASS represents reanalysis or General Circulation Model (GCM) winds as 3D mass transports between grid boxes by solving the continuity equation.…”
Section: Tracking Air Back In Time With Tracmass-era5mentioning
confidence: 99%
“…To follow the evolution of the air masses of the hot events backwards in time, we employ the Lagrangian trajectory model TRACMASS v7.0 (Aldama-Campino et al, 2020;Döös, 1995), which can be applied to study the atmospheric or oceanic circulation (e.g., Dey & Döös, 2020;Liang & Xue, 2020). TRACMASS represents reanalysis or General Circulation Model (GCM) winds as 3D mass transports between grid boxes by solving the continuity equation.…”
Section: Tracking Air Back In Time With Tracmass-era5mentioning
confidence: 99%
“…Observation of NIIW recirculation within the Savu Sea and its possible intrusion into Banda Sea via the northern and eastern portal of the Ombai Strait are still a challenge. However, recent model study suggested that a reversal throughflow via Ombai Strait brings Indian intermediate water into interior seas and farther into the western tropical Pacific Ocean(Liang et al, 2020).4. CONCLUSIONSThe INDOMIX cruise, carried out in July 2010, provides a unique dataset to document water masses and currents along the track from the edge of the Pacific Ocean to the Halmahera entry portal to the southern Lesser Sunda Arc, successively crossing the Seram Sea, Manipa Strait, Banda Sea, Ombai Strait, northern Savu Sea, Sumba Strait, and south of Lombok Strait.…”
mentioning
confidence: 99%
“…Nested within a large‐region physical model, the small‐region physical model off the southern coast of Java Island resembles the seasonal cycle of depth‐integrated transport from the surface to 300 m through the Lombok section revealed by INSTANT data (Sprintall et al., 2009), which peaks at ∼4 Sv from July to September and decreases to a minimum of ∼2 Sv in December and January in concert with monsoons and transitions (Liang & Xue, 2020). Well‐characterized ITF transport through the Lombok section plays an important role in modeling the circulation and nutrient transport off the southern coast of Java Island (see more details in Section 6).…”
Section: Comparison Of the General Characteristics Between The Model ...mentioning
confidence: 99%